Case report: a delayed diagnosis of Turner’s syndrome in aboriginal adolescence in primary care - Thew, Hui Zhu; Fong, Yan Bin; Fong, Wen Yuan; Loo, Cheng Yee; Choy, Ja Shen; Ng, Chee Han (Universiti Putra Malaysia Press, 2024)
Turner syndrome is a genetic disorder characterized by a partial or complete loss of one X chromosome in females. This case report describes a 16-year-old Aboriginal adolescent who presented with amenorrhea and developmental challenges in primary care on a community visit. The patient's medical history revealed a delay in speech development, poor academic performance, and limited literacy skills. Physical examination demonstrated characteristic Turner Syndrome features such as slanted eyes, a flat nasal bridge, a webbed neck, cubitus valgus, short metatarsals, and atrophic genitalia. Karyotyping confirmed the diagnosis of Turner Syndrome (45, X). In addition, the patient exhibited growth retardation, with height and weight measurements below the 3rd centile. Management included a referral to obstetrics and gynaecology for growth hormone therapy, aortic aneurysm and bone marrow density monitoring, and genetic counselling for the family. This case emphasizes the importance of early diagnosis, the challenges in diagnosing TS in rural areas and multidisciplinary care for patients with Turner Syndrome to address the condition's medical and developmental aspects.